2022
DOI: 10.1002/adfm.202205974
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Performance of Bi2S3 in Electrocatalytic and Supercapacitor Applications by Controlling Lattice Strain

Abstract: Lattice‐strained Bi2S3 with 3D hierarchical structures are prepared through a top‐down route by a topotactic transformation. High‐resolution transmission electron microscopy and X‐ray diffraction (XRD) confirm the lattice spacing is expanded by prolonged sulfuration. Performance studies demonstrate that Bi2S3 with the largest lattice expansion (Bi2S3‐9.7%, where 9.7% represents the lattice expansion) exhibits a greater electrocatalytic hydrogen evolution reaction (HER) activity compared to Bi2S3 and Bi2S3‐3.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…The high-resolution deconvolution XPS spectra of Bi 4f in Bi 2 S 3 nanorods (Figure c) displayed peaks at 163.2 and 157.9 eV associated with Bi 4f 5/2 and Bi 4f 7/2 , respectively. The two peaks at 161.9 and 160.5 eV in the high-resolution deconvolution XPS spectra of S 2p corresponded to S 2p 1/2 and S 2p 3/2 , respectively, confirming the formation of the Bi–S structure . As for the XPS of Bi 2 S 3 –BaTiO 3 , the peaks of Ba 3d 3/2 and Ba 3d 5/2 were located at 794.7 and 779.3 eV, respectively (Figure d).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The high-resolution deconvolution XPS spectra of Bi 4f in Bi 2 S 3 nanorods (Figure c) displayed peaks at 163.2 and 157.9 eV associated with Bi 4f 5/2 and Bi 4f 7/2 , respectively. The two peaks at 161.9 and 160.5 eV in the high-resolution deconvolution XPS spectra of S 2p corresponded to S 2p 1/2 and S 2p 3/2 , respectively, confirming the formation of the Bi–S structure . As for the XPS of Bi 2 S 3 –BaTiO 3 , the peaks of Ba 3d 3/2 and Ba 3d 5/2 were located at 794.7 and 779.3 eV, respectively (Figure d).…”
Section: Resultsmentioning
confidence: 66%
“…This intimate contact was highly conducive to electron transfer in Bi 2 S 3 –BaTiO 3 . At the same time, there were slight shifts in the split peak positions of Bi 4f and S 2p for Bi 2 S 3 –BaTiO 3 compared to Bi 2 S 3 , indicating a mutual interaction between BaTiO 3 and Bi 2 S 3 . , …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Preferentially exposing some specific faces with high energy can increase the reaction rate. [25][26][27] For example, Wang and co-workers proposed an in situ electrochemical reduction strategy to synthesize Pt nanosheets with high-index {311} planes and low-index {200} and {111} planes on carbon nanotubes, and it is found that the {311} planes of Pt nanosheets had a higher electrocatalytic hydrogen evolution activity compared with the other planes. [28] Kuo et al prepared {100} facet-dominated silver nanocubes and {111} facetdominated silver nano octahedra via polyol reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al . have reported the lattice-strained Bi 2 S 3 with 3D hierarchical structure in an asymmetric supercapacitor, exhibiting a high specific capacitance of 307.4 F g –1 . Bi 2 Se 3 has been recognized as an efficient host material for lithium/sodium/zinc ions. Furthermore, Bi 2 O 2 Se has been studied in zinc-ion batteries and showed good electrochemical performance toward H + and Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%